2018
DOI: 10.21620/ijfaas.2017264-75
|View full text |Cite
|
Sign up to set email alerts
|

Magnetite (Fe3O4) - Synthesis, Functionalization and its Application

Abstract: Nanoparticles are smaller than 100nm. Size of particle depends upon the method that is used for synthesis of nanoparticles. Magnetic nanoparticles consist of iron, cobalt and nickel and their chemical compounds. Their safety or toxicity is major concern for use in food. Magnetite, hematite and meghemite are types of magnetic nanoparticles. Magnetite (Fe 3 O 4 ) common among the magnetic iron oxide nanoparticle that is used in food industry. Magnetite is getting popular due to its super paramagnetic properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Pristine H-NPs and M-NPs are still precluded and hampered for niche electrochemical and PEC environmental-related applications owing to their relatively poor electron conductivity, short hole diffusion length, fast photoexcitons, and limited absorption coefficient. , Additionally, upon contact with air (O 2 and moisture), these NPs could experience some serious physicochemical and compositional changes. For example, M-NPs lose some magnetism and monodispersibility when contacted with air for a longer time . Therefore, various efforts are required to overcome these challenges and hence their potential implications in awaiting advanced applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pristine H-NPs and M-NPs are still precluded and hampered for niche electrochemical and PEC environmental-related applications owing to their relatively poor electron conductivity, short hole diffusion length, fast photoexcitons, and limited absorption coefficient. , Additionally, upon contact with air (O 2 and moisture), these NPs could experience some serious physicochemical and compositional changes. For example, M-NPs lose some magnetism and monodispersibility when contacted with air for a longer time . Therefore, various efforts are required to overcome these challenges and hence their potential implications in awaiting advanced applications.…”
Section: Discussionmentioning
confidence: 99%
“…For example, M-NPs lose some magnetism and monodispersibility when contacted with air for a longer time. 149 Therefore, various efforts are required to overcome these challenges and hence their potential implications in awaiting advanced applications. The physicochemical properties of these NPs can be tuned to increase their suitability for various applications.…”
Section: Discussionmentioning
confidence: 99%
“…The last, biological method involves plan mediated, fungi mediated, bacteria mediated, and protein-mediated (Ali, et al, 2016). Among those methods, chemical coprecipitation is considered very appropriate method for synthesizing the Fe 3 O 4 nanoparticles due to its simple procedure, short reaction time, high yield, low synthesis temperature (20 o C -150 o C), relatively narrow size distribution, and cost-effective (Ramadan, et al, 2011;Ali, et al, 2016;Ghazanfari, et al, 2016;Hameed, et al, 2017). (Reddy & Yun, 2016) In this study, we reported the effect of synthesis temperature and NaOH concentration on the microstructure and optical properties of the Fe 3 O 4 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical stability and possible chemical adaptation by coating the iron oxide cores with several kinds of layers (e.g., silica, gold, and polymers ) can be regarded as desirable properties attributed to iron oxide nanoparticles and they are considered as the individual kind of MNPs that have been accepted by the FDA for medical applications. 19,20 The current research aimed to improve a magnetite poly-єcaprolactone-functionalized nanoparticulate (PCL-MNP) system for drug delivery that could carry and release the drugs over long times. INH is regarded as one of the most important drugs which are widely used in the treatment programs for TB.…”
Section: Introductionmentioning
confidence: 99%